Understanding the link with Customer Relationship Management (CRM) - Balaraman, Pravin (Henry Stewart Talks, 2010)
Emergence of Customer Relationship Management (CRM), The four Ps of CRM, The importance of CRM, Return on investment (ROI) on CRM, Problems experience with ROI, Barriers to CRM, The major challenges to CRM